Proposta de ensino sobre ligas metálicas: abordagem investigativa acerca do patrimônio cultural de Araras – SP - Santos, Thiago Elias dos (Universidade Federal de São Carlos, 2025)
This paper proposes an innovative approach to teaching chemistry about metallic alloys, through a didactic sequence aimed at students in the first year of secondary school in Basic Education and also at those studying Materials Science in the Chemistry degree course in Higher Education, through an investigative approach to the cultural heritage of Araras-SP, specifically the railway lines. The topic provides a link between the city in question and chemistry in the educational context, enhancing the importance of the Federal University of São Carlos for the area. This link can be explored through the railway sector, which for the moment is mostly in ruins, showing the neglect and consequently the carelessness of the administration. The proposal is to use this context to bring the university and the community closer together, promoting quality education through active methodologies, which emphasize the effective and main participation of students in learning, while the teacher acts as a mediator in an interdisciplinary perspective. The Investigative Approach, in particular, proves to be prosperous for future chemistry teachers, broadening their pedagogical perspectives. Although the proposal is innovative for teaching chemistry about metal alloys, it is worth noting that it has not yet been applied, and it is worth suggesting its implementation in future work, making it possible to evaluate its efficiency and identify challenges in order to improve it.
Teaching proposal on metal alloys: investigatice approach on the cultural heritage of Araras-SP
Keywords: Patrimônio cultural; Abordagem investigativa; Ligas metálicas; Cultural heritage; Research-based teaching; Metal alloys; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM